I understand your pain but I do not feel it: lower affective empathy in response to others’ social pain in narcissism - Shahri, Fatemeh; Zabihzadeh, Abbas; Taqipanahi, Alireza; Haromi, Morteza Erfani; Rasouli, Mobina; Saeidi Nik, Asal; Eddy, Clare M. (Frontiers in Psychology, 2024)
While the relationship between narcissism and empathy has been well-researched, studies have paid less attention to empathic accuracy i.e. appreciating the precise strength of another person's emotions, and self-other distinction, in terms of the disparity between affective ratings for self and other in response to emotive stimuli. Furthermore, empathic responses may vary depending on whether the pain is physical or social. We investigated empathic accuracy, affective empathy, and the distinction between pain, emotion and intensity ratings for self and other, in high (n=44) and low (n=43) narcissism groups (HNG and LNG, respectively) selected from 611 students, in response to both types of pain. Participants watched six videos where targets expressed genuine experiences of physical and social pain, and rated the perceived affect and pain experienced by the person in the video and their own empathic emotional responses. The HNG displayed lower affective empathy and empathic accuracy than the LNG for both pain types. Within the HNG there was higher empathic accuracy for social versus physical pain, despite reduced affective empathy for social pain, in contrast to the LNG. In addition to this paradox, we found evidence of lower emotional resonance in more highly narcissistic individuals, suggesting higher self-other distinction in response to viewing targets describing social pain.